2021
DOI: 10.1111/jgh.15468
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin versus furazolidone for naïve Helicobacter pylori infected patients in a high clarithromycin resistance area

Abstract: Background and Aim The increase in antibiotic resistance makes the eradication of Helicobacter pylori more difficult. Considering the limitations of the application of susceptibility‐guided therapy, it is important to find an effective empirical regimen. The aim of the study is to compare the efficacy, safety, and cost‐effectiveness of clarithromycin‐based bismuth‐containing quadruple therapy (C‐BQT) and furazolidone‐based bismuth‐containing quadruple therapy (F‐BQT) in naïve H. pylori positive patients. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…Amoxicillin, clarithromycin, levofloxacin, and furazolidone are frequently used antibiotics in the first-line treatment of H. pylori in China. 10,11 The trend of rising rates of resistance to antibiotics in H. pylori strains and its multiple resistance patterns increases the difficulty of eradication treatment in the clinic. 15 Therefore, despite bismuth-containing quadruple therapy being adopted, initial clinical empirical medical practice in these regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amoxicillin, clarithromycin, levofloxacin, and furazolidone are frequently used antibiotics in the first-line treatment of H. pylori in China. 10,11 The trend of rising rates of resistance to antibiotics in H. pylori strains and its multiple resistance patterns increases the difficulty of eradication treatment in the clinic. 15 Therefore, despite bismuth-containing quadruple therapy being adopted, initial clinical empirical medical practice in these regions.…”
Section: Discussionmentioning
confidence: 99%
“…9 In China, amoxicillin, levofloxacin, furazolidone, and clarithromycin are the most frequently used antibiotics constituting these regimens. 10,11 The process of antibiotic resistance of H. pylori is evolving and dynamic. The status of antibiotic sensitivity and type of resistance seriously affects the success rate of initial eradication therapy in clinical patients.…”
Section: Introductionmentioning
confidence: 99%
“…FZD is a nitrofuran antibiotic effective against gram-negative and -positive bacteria[ 27 ]. Qiao et al [ 28 ] reported that an FZD-based BQT showed a similar first-line H. pylori eradication rate in PP analysis to a CAM-based BQT (95.8% vs 93.4%). The resistance rates of H. pylori to AMX, TET, and FZD remain low in China at < 5%[ 29 ].…”
Section: Recommended H Pylori Regimensmentioning
confidence: 99%
“…Although there are many highly effective treatment regimens, 6,7 only around 70% of initial cases are successfully eradicated. 8 Many factors contribute to this limited rate, especially including poor compliance.…”
Section: Introductionmentioning
confidence: 99%
“…pylori eradication rate is unsatisfactory. Although there are many highly effective treatment regimens, 6,7 only around 70% of initial cases are successfully eradicated 8 9–12 .…”
Section: Introductionmentioning
confidence: 99%